A development bank's choice of private equity partner: a behavioural game-theoretic approach. Issue 16 (2nd November 2019) - Fairchild, Richard; Crawford, Ian; El-Fakir, Adil
ABSTRACT: We develop a formal game-theoretic analysis of the economic (value-adding abilities) and behavioural factors (empathy, emotional excitement, passion) affecting a development bank's choice of private-equity partner when investing into emerging market entrepreneurship. Triple-sided moral hazard (TSMH) problems occur in the form of effort-shirking, since the bank, the PE-manager, and the entrepreneur all contribute to value-creation. The bank's investment choices are crucially affected by a) the relative abilities and the potential level of empathy, excitement and passion that may be generated between a PE-manager and an entrepreneur, and b) the personal emotional attachment that the bank develops towards a PE. The severity of TSMH increases inefficiencies in decision-making. Finally, we consider, in addition to political risk mitigation, an additional impact that the bank may have on PE/E value-creation: the bank may have a coaching/mentoring role. Our analysis has implications for academics and practitioners alike.